2009
DOI: 10.1387/ijdb.082643pm
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian hibernation: differential gene expression and novel application of epigenetic controls

Abstract: This review highlights current information about the regulatory mechanisms that govern gene expression during mammalian hibernation, in particular the potential role of epigenetic controls in coordinating the global suppression of transcription. Hibernation is characterized by long periods of deep torpor (when core body temperature drops to near ambient) that are interspersed with brief arousal periods back to euthermia. Entry into torpor requires coordinated controls which strongly suppress and reprioritize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 96 publications
(93 reference statements)
2
73
0
Order By: Relevance
“…Indeed, the study of mammals that are able to alternate between two extremely different physiological states (i.e. hibernation) has shed some light on a wide array of potential epigenetic controls of metabolic rate suppression (Morin and Storey, 2009). Also consider, for example, that biologists generally assume that any paternal contribution to epigenetic effects is strictly through the germ line, because in many animals little other than the sperm and some modest amounts of supporting fluids are transferred at mating.…”
Section: Additional Mechanisms For Transgenerational Transfer?mentioning
confidence: 99%
“…Indeed, the study of mammals that are able to alternate between two extremely different physiological states (i.e. hibernation) has shed some light on a wide array of potential epigenetic controls of metabolic rate suppression (Morin and Storey, 2009). Also consider, for example, that biologists generally assume that any paternal contribution to epigenetic effects is strictly through the germ line, because in many animals little other than the sperm and some modest amounts of supporting fluids are transferred at mating.…”
Section: Additional Mechanisms For Transgenerational Transfer?mentioning
confidence: 99%
“…Histone modifications include acetylation and phosphorylation, which reduce chromatin packing to increase transcription factor accessibility to gene promoters, and methylation, which acts oppositely. In hibernating mammals, relative levels of histone acetylation and phosphorylation decrease during torpor and activities of histone deacetylases rise, all indicative of transcriptional silencing (Morin and Storey, 2009). Only one study to date has approached epigenetic regulation in aestivation.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Another group has also illustrated that the expression of multiple miRNAs was significantly altered following the exposure of human articular chondrocytes to hyperosmotic conditions [31]. Apart from these, a study investigating the possible role of miRNAs in the regulation of mammalian hibernation found that miR-1 and miR-21 were both significantly increased in the kidneys of hibernating versus euthermic animals, providing the first evidence of differential expression of miRNAs in response to temperature control in mammals [32]. Taken together, these studies support the notion that miRNA regulation in response to microenvironmental changes may contribute to cellular physiology and abnormality of such regulation may be involved in pathological processes.…”
Section: Mirnas and Alterations Of Their Expression In Response To MImentioning
confidence: 99%